Índice de massa corporal e circunferência abdominal entre adolescentes no interior do Piauí, Brasil - Moura, Ionara Holanda de (2012)
Anthropometric techniques, establishing the diagnosis of overweight / obesity as body mass index (BMI) and waist circumference (WC), are increasingly important. With this research we aimed to learn about BMI and relate it to the WC of adolescent students in two institutions in Piaui. This descriptive cross-sectional study of quantitative prevalence. It carried out in two public schools in Picos - PI with 145 adolescents aged between 12 and 18 years for both sexes. Data collection was performed through a form from the months of August to December 2010. The prevalence of overweight was 3.7%. Overweight was significantly associated with increased WC (<0.0001). These results emphasize the relevance of conducting prevention and control of excess weight so that the health of adolescents should be maintained.